Escolhas e usos do livro didático de arte: perspectivas de professores - Scorteganha, Amábile Cristina Novaes (2020)
The theme of this study deals with the choices and the uses of Art textbooks (AT), due to their recent selection, acquisition and distribution within the Programa Nacional do Livro e do Material Didático (PNLD) (National Textbook and Didactic Materials Program), for the Brazilian public schools. The general objective is to analyze the choice processes and the uses of the Art textbook from the perspective of teachers from the public network of the city of Passo Fundo/RS. The research has as specific objectives: a) to analyze the criteria used by the teachers to choose the AT; b) to understand if the assessment of textbooks was done during the teachers education; c) to assess the relation between the conceptions of Art teaching and the uses of the AT; and d) to problematize the polyvalent character existing in the AT. The adopted methodology is a qualitative investigation that consists in the study of multiple cases, approaching the theme of the Art textbook. The research had as a starting point, a bibliographic review in thesis, dissertations, annals and articles published in magazines and periodicals. This way, two data production strategies were developed: document analysis and semi-structured interviews. For the document analysis the Edital de Convocação do PNLD 2017 (Public Notice of Assembly of PNLD 2017), the Guia de Livros Didáticos de Arte (Art Textbooks Guidelines) and the elementary school AT selected in the scope of the PNLD 2017 were used. The semi-structured interviews were done in exploratory visits with the Textbook Advisor, in the 7ª Coordenadoria Regional de Educação (CRE) (7th Regional Education Coordination Office), with the Coordinator of the Núcleo do Ensino Fundamental (Coordinator of the Elementary School Center), in the Secretaria Municipal de Educação (SME) (City Department of Education), as well as 10 teachers from the public network of the city of Passo Fundo/RS, with specific graduation in one of the fields of Art, who accepted to answer questions about the choice processes and uses of the AT. For the study of the found data, analysis categories were established in the perspective of technical content analysis, according to Amado et al. (2013), namely: 1) The reception of the AT by the teachers; 2) The Art teacher education in relation to the AT; 3) The choice processes of the AT; 4) The uses of the AT and other didactic materials; 5) The assessment of the AT in the Teaching Perspective. The results show that the criteria adopted for the choice of the AT, by the interviewed Art teachers, are guided, among others, in the alignment of the contents to their planning, in the conceptions of Art teaching presented in the books, in the text diagram and in the quality of the images and reading scripts, evidencing that the Guia de Livros Didáticos (Textbook Guidelines) was not a deciding factor in the choice processes. In relation to the uses of the AT by these teachers, it was noted that they occur mainly during the planning moments and, in class, specifically with the selection of some contents to be approached with the students, such as text reading and the study of the images presented. Therefore, it is concluded that the AT occupies a limited space and partial position in the classes of the Art curriculum of the final years of the elementary level of Passo Fundo’s public schools, based on the reports that showed a non-central role in its use inside the classroom with the students.